2021
DOI: 10.1093/gerona/glab189
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vascular Risk Scores and Cognitive Performance in a Diverse Cohort: The Multi-Ethnic Study of Atherosclerosis

Abstract: Background Vascular risk scores are associated with incident dementia. Information regarding their association with cognitive performance and decline in racially/ethnically diverse cohorts is lacking. Methods In 4392 Multi-Ethnic Study of Atherosclerosis participants (aged 60.1±9.4 years; 53% women; 41% white, 11% Chinese-American, 26% African-American, 21% Hispanic), we compared associations of Exam 1 (2000-02) Cardiovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…These findings extend recent work from our group which showed that these same conventional clinical risk scores for CHD, stroke, and CAIDE were significantly associated with cross sectional cognitive performance, cognitive decline over 6 years, as well as, lower cortical thickness, greater white matter hyperintensity burden, and amyloid deposition on neuroimaging in this MESA cohort. 5,6 Taken together, this work suggests the potential research utility of including subclinical pathways of vascular risk in future work looking at the vascular contributions to cognitive impairment and dementia.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…These findings extend recent work from our group which showed that these same conventional clinical risk scores for CHD, stroke, and CAIDE were significantly associated with cross sectional cognitive performance, cognitive decline over 6 years, as well as, lower cortical thickness, greater white matter hyperintensity burden, and amyloid deposition on neuroimaging in this MESA cohort. 5,6 Taken together, this work suggests the potential research utility of including subclinical pathways of vascular risk in future work looking at the vascular contributions to cognitive impairment and dementia.…”
Section: Discussionmentioning
confidence: 82%
“…Standard vascular risk scores for each MESA participant were calculated using published equations including the Atherosclerotic Cardiovascular Disease -Pooled Cohort Equation (ASCVD-PCE), 9 Framingham Global CVD risk score (FRS), 10 Framingham 10year Stroke Risk Score (FRS-Stroke), 11 and Cardiovascular Risk Factors, Aging, and Incidence of Dementia (CAIDE) 12 drawn from questionnaire and clinical examination during the MESA Exam 1 visit as previously described. 5 Subclinical cardiovascular assessments at baseline included: carotid ultrasound for carotid plaque, adventitial diameter, and intima-media thickness; 13,14 coronary artery calcium score by cardiac computed tomography; 15 augmentation index, large and small artery elasticity, total vascular impedance, estimated cardiac output, stroke volume, and radial tonometry. 16 Cardiac MRI and brachial flow mediated dilation were only completed on a subset of participants at the baseline examination.…”
Section: Demographic Clinical and Subclinical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies focused on identifying biological mechanisms that generate racial disparities have revealed that Black and White patients with dementia demonstrate different neuropathological changes, suggesting differences in the manifestations of the underlying pathophysiological processes 39,40 . Observational studies of diverse cohorts demonstrate important differences in vascular and metabolic risk factors for AD/ADRD and their treatment that may explain excess risk in both mortality and ADRD among Black and Hispanic older adults 41–44 . However, although biological and genetic factors are associated with higher AD/ADRD risk in certain racial groups, 2 social determinants of health account for more than half of the variance in health outcomes 45 …”
Section: Race/ethnicity‐related Disparitiesmentioning
confidence: 99%
“…39,40 Observational studies of diverse cohorts demonstrate important dif-ferences in vascular and metabolic risk factors for AD/ADRD and their treatment that may explain excess risk in both mortality and ADRD among Black and Hispanic older adults. [41][42][43][44] However, although biological and genetic factors are associated with higher AD/ADRD risk in certain racial groups, 2 social determinants of health account for more than half of the variance in health outcomes. 45 Future studies of race/ethnicity-related disparities in AD/ADRD should focus on remedying the limitations described above.…”
Section: Us-born Vs Foreign-born)mentioning
confidence: 99%